2021
DOI: 10.1038/s41591-021-01455-x
|View full text |Cite|
|
Sign up to set email alerts
|

Safety and efficacy of anti-tau monoclonal antibody gosuranemab in progressive supranuclear palsy: a phase 2, randomized, placebo-controlled trial

Abstract: A randomized, double-blind, placebo-controlled, 52-week study (NCT03068468) evaluated gosuranemab, an anti-tau monoclonal antibody, for progressive supranuclear palsy (PSP). In total, 486 participants dosed were assigned to gosuranemab (n=321) or placebo (n=165).Efficacy was not demonstrated on adjusted mean change of PSP Rating Scale score at week 52 between gosuranemab and placebo (10.4 versus 10.6; P=0.85; primary endpoint) or secondary endpoints, resulting in discontinuation of the open-label long-term ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
48
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 76 publications
(52 citation statements)
references
References 62 publications
1
48
2
Order By: Relevance
“…Gosuranemab is a humanized monoclonal antibody against extracellular N-terminal of tau in the interstitial fluid (ISF) and CSF released by neurons. A phase II trial in progressive supranuclear palsy showed that the unbound N-terminal tau in CSF was decreased by 98% in the gosuranemab group and increased by 11% in the placebo group, but the N-terminal tau neutralization does not translate into clinical efficacy (NCT03068468) [ 72 ]. Recently, Kim and his colleagues examined the brain tissues of three individuals receiving gosuranemab and found that gosuranemab treatment may be associated with glial responses including accumulation of tau within astrocytic lysosomes [ 73 ].…”
Section: Immunotherapies Based On Tau Proteinmentioning
confidence: 99%
“…Gosuranemab is a humanized monoclonal antibody against extracellular N-terminal of tau in the interstitial fluid (ISF) and CSF released by neurons. A phase II trial in progressive supranuclear palsy showed that the unbound N-terminal tau in CSF was decreased by 98% in the gosuranemab group and increased by 11% in the placebo group, but the N-terminal tau neutralization does not translate into clinical efficacy (NCT03068468) [ 72 ]. Recently, Kim and his colleagues examined the brain tissues of three individuals receiving gosuranemab and found that gosuranemab treatment may be associated with glial responses including accumulation of tau within astrocytic lysosomes [ 73 ].…”
Section: Immunotherapies Based On Tau Proteinmentioning
confidence: 99%
“…Furthermore, subtypes of PD were not considered in most PD trials (Pagano et al 2021 ; Rascol et al 2011 ). Recent trials in PSP enrolled patients according to the previous NINDS-SPSP diagnosis criteria (Höglinger et al 2021 ) or by the presence of postural instability and vertical gaze palsy (Dam et al 2021 ) and thereby de facto only included patients with a Richardson-syndrome without taking into account that these only comprise a quarter of all PSP patients (Respondek and Höglinger 2016 ). In MSA, some trial only included patients with predominant Parkinsonism (Dodel et al 2010 ), whereas other trials included patients with MSA-C and MSA-P (Bensimon et al 2009 ; Levin et al 2016b , 2019 ).…”
Section: Studies With the Aim To Investigate Neuroprotectionmentioning
confidence: 99%
“…There have been several large antibody-based clinical trials for CNS disorders. Dam et al [ 140 ] examined the safety and efficacy of an anti-tau antibody (gosuranemab) for progressive supranuclear palsy (NCT03068468). However, the phase II trial failed to show evidence of neurologic efficacy even though unbound N-terminal tau levels in CSF decreased by 98%.…”
Section: Drug Deliverymentioning
confidence: 99%